Assessing the potential of low-cost minerals for the removal of hexavalent chromium from groundwater: a case study from Ukraine - Trach, Yuliia (Frontiers in Environmental Chemistry, 2025)
This study investigated the feasibility of passively treating acidic Cr6+ wastewater and reducing the migration of toxic Cr3+ using locally sourced, low-cost minerals from the mining industry, which are either waste products or secondary raw materials. Iron-rich aluminosilicates, quartz-glauconite sand (18% glauconite), volcanic tuff (30% chlorite and 10% pyroxene), and glauconite concentrate (70%) were evaluated in combination with limestone. Cr6+ reduction experiments were conducted at varying dosages (10–50 g/L) of the test materials in batch experiments, with changes in pH (initial 3.2), Eh, and total dissolved solids measured. Natural limestone (0–20 mm), sourced from an active limestone quarry in the Ternopil region, Ukraine, was used to assess its feasibility in reducing the migration of Cr3+ formed during Cr6+ reduction. The results demonstrated that the greatest Cr6+ reduction was achieved using a combination of volcanic tuff and quartz-glauconite sand. Both batch and column studies indicated that limestone effectively reduced Cr3+ concentrations by raising the water’s pH to the range of 7.8–8.2, aiding in its immobilization. Overall, the study confirmed the feasibility of utilizing local mining waste as valuable and cost-effective reagents or adsorbents for the highly toxic Cr6+. These findings enabled the development of practical recommendations for employing iron-rich aluminosilicates in combination with limestone.